EVALUASI PENGARUH COUNTRY-OF-ORIGIN, MEREK, DAN HARGA PADA PEMBELIAN PRODUK SUSU IMPORT - W Mahestu Noviandra Krisjanti (KINERJA, 2007)
Indonesian people tend to prefer and have a good perception about imported products compare to the domestic products. Indeed, when they don’t have any competence to judge the quality of the product they will use country-of-origin, brand and also the price as a basic. Therefore, this research will evaluate those three variables in imported product buying decision, in the case of imported infant milk. The research will analyze whether mother as the decision maker of this product is influenced by country-of-origin, brand and price. From the data analysis, it is found that only price and brand which influence the buying decision. Country-of-origin doesn’t influence the buying decision significantly.Keywords: country-of-origin, harga, merek, susu bayi import